2020
DOI: 10.3389/fimmu.2020.00611
|View full text |Cite
|
Sign up to set email alerts
|

Human Regulatory T Cells From Umbilical Cord Blood Display Increased Repertoire Diversity and Lineage Stability Relative to Adult Peripheral Blood

Abstract: Tregs. Interestingly, expression of canonical Treg markers, such as FOXP3, TIGIT, and IKZF2, were increased in CB CD4 + CD127 + conventional T cells (Tconv) compared to APB Tconv, post-expansion, implying perinatal T cells may adopt a default regulatory program. Collectively, these data identify surface markers (namely CXCR3) that could be depleted to improve purity and stability of APB Tregs, and support the use of expanded CB Tregs as a potentially optimal ACT modality for the treatment of autoimmune and inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 150 publications
2
25
0
Order By: Relevance
“…And found that both CD25+ cells at day 0 and iTregs at day 21 expressed all the 24 TCRs ( 30 ). In addition, Motwani et al demonstrated that effector Tregs could clonally expand in the late decidua during normal pregnancy, but could not expand in peripheral blood of humans ( 62 ). Therefore, the expanded iTreg cells were mainly transformed from CD4+CD25+ T cells rather than pTreg proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…And found that both CD25+ cells at day 0 and iTregs at day 21 expressed all the 24 TCRs ( 30 ). In addition, Motwani et al demonstrated that effector Tregs could clonally expand in the late decidua during normal pregnancy, but could not expand in peripheral blood of humans ( 62 ). Therefore, the expanded iTreg cells were mainly transformed from CD4+CD25+ T cells rather than pTreg proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The shorter TCRs in neonatal T cells do not limit TCR diversity. The results from deep sequencing and single cell sequencing demonstrate higher diversity of TCR repertoire in human neonatal Tconv and Tregs when compared to adult ones ( 28 , 29 ). In addition, UCB Treg cells are also shown to have more clones with TCRs specific for autoantigens ( 28 ).…”
Section: T Cell Repertoire Before Thymic Selection In Early Lifementioning
confidence: 97%
“…Indeed, specific and competent CD8 + T cell responses against a range of viral infections (Vesicular Stomatitis Virus, Vaccinia Virus, and Lymphocytic Choriomeningitis Virus) in vivo have been observed in murine Tdt -deficient or neonatal T cells ( 34 , 43 , 44 ). In human samples, T cells in UCB had higher level of CD5 expression and higher precursor frequency for certain tumor-associated antigens or pathogens than T cells in adults ( Table 1 ) ( 28 , 42 , 45 ). Together with delayed TdT expression and similar TCR sequencing feature between human fetal T cells and mouse neonatal T cells, it is believed, although more evidence is needed, that human TCR repertoire also has high cross-reactivity.…”
Section: T Cell Repertoire Before Thymic Selection In Early Lifementioning
confidence: 99%
“…Alternative sources and methods for expansion of Tregs that maintain their intrapopulational heterogeneity and retention of CD62L-positive, less differentiated Tregs should be investigated. Interestingly, umbilical cord Tregs exhibit increased repertoire diversity and are better at maintaining Treg lineage stability (73). It is possible that the naive source of Tregs from umbilical cords and improved expansion methods could lead to longer-lasting Tregs that retain their suppressive capacity.…”
Section: Exogenous Treg Therapymentioning
confidence: 99%